Simulating the influences of groundwater on regional geomorphology using a distributed, dynamic, landscape evolution modelling platform. (December 2015) - Barkwith, Andrew; Hurst, Martin D.; Jackson, Christopher R.; Wang, Lei; Ellis, Michael A.; Coulthard, Tom J.
Abstract: A dynamic landscape evolution modelling platform (CLiDE) is presented that allows a variety of Earth system interactions to be explored under differing environmental forcing factors. Representation of distributed surface and subsurface hydrology within CLiDE is suited to simulation at sub-annual to centennial time-scales. In this study the hydrological components of CLiDE are evaluated against analytical solutions and recorded datasets. The impact of differing groundwater regimes on sediment discharge is examined for a simple, idealised catchment, Sediment discharge is found to be a function of the evolving catchment morphology. Application of CLiDE to the upper Eden Valley catchment, UK, suggests the addition of baseflow-return from groundwater into the fluvial system modifies the total catchment sediment discharge and the spatio-temporal distribution of sediment fluxes during storm events. The occurrence of a storm following a period of appreciable antecedent rainfall is found to increase simulated sediment fluxes. Highlights: Integration of a coupled hydrological component into a landscape evolution model. Baseflow-return can transition morphology between differing steady-states. Model used to assess the role of groundwater in shaping regional geomorphology. Groundwater alters the distribution of sediment flux during storm events.